2019
DOI: 10.1563/aaid-joi-d-19-00140
|View full text |Cite
|
Sign up to set email alerts
|

Photogrammetric and Intraoral Digital Impression Technique for the Rehabilitation of Multiple Unfavorably Positioned Dental Implants: A Clinical Report

Abstract: The aim of this clinical report is to describe the use of the photogrammetric system and intraoral scanning as a reliable technique to record the 3-dimensional implant positions of a full-arch maxillary implant–supported fixed rehabilitation in which the implants were unfavorably positioned. The stereo camera of the photogrammetric system was used to capture the 3-dimensional panoramic position of the implants. The information on soft tissues was obtained with an intraoral scanner. Then, the 2 digital files (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
0
11
0
6
Order By: Relevance
“…The major limit of the intraoral scanner is its high cost. Furthermore, doctors and operators have to learn quite complex skills required to master the machine with confidence [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The major limit of the intraoral scanner is its high cost. Furthermore, doctors and operators have to learn quite complex skills required to master the machine with confidence [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, photogrammetry has gradually become popular in clinical practice. The digital file of the 3D position of the implant captured using photogrammetry technology can be superimposed on the soft tissue data acquired by the intraoral scanner to obtain an accurate impression of the edentulous implant 202 . But the combined use of multiple devices also implies that more biases are introduced.…”
Section: Applications Of 3d Imaging Devicesmentioning
confidence: 99%
“…In a randomized clinical trial, Peñarrocha-Diago et al reported that stereophotogrammetric and traditional impressions showed no differences in implant success rate, marginal bone loss, or prosthesis survival after one year of follow-up [27]. In addition, numerous clinical reports also stated that this technique ensures optimum fit of the framework representing a predictable solution for complete implant-supported cases [28][29][30][31][32][33]. Although new technologies are based on the premise of achieving higher quality prosthesis, their direct comparison with digital intraoral scanning is still lacking robust evidence in the literature (specifically with tilted implants) [34][35][36].…”
Section: Introductionmentioning
confidence: 99%